2017
DOI: 10.1186/s12885-017-3597-6
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence in eastern Morocco: cancer patterns and incidence trends, 2005–2012

Abstract: BackgroundCancer is one of the major health problems worldwide. In this article, we present for the first time the cancer incidence trends, the distribution and the socioeconomic profile of incident cancer cases in Eastern Morocco over a period of eight years.MethodsRetrospective descriptive study of patients diagnosed with cancer at the Hassan II Regional Oncology Center (ROC) since it was created in October 2005 until December 2012. During the study period, the ROC was the only hospital specialized in cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…In our study, the mean age of patients was slightly higher in men (53.48 years) than in women (52.39 years). The same results have been reported in several studies [10,11,14,15].…”
Section: Treatment Details and Outcomessupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, the mean age of patients was slightly higher in men (53.48 years) than in women (52.39 years). The same results have been reported in several studies [10,11,14,15].…”
Section: Treatment Details and Outcomessupporting
confidence: 91%
“…The majority of patients in the study were female. This feminine predominance has already been reported in Togolese patients by Amégbor [7] and has also been observed in other studies in Africa [9,12,15]. This can be explained by the large proportion of breast and cervix cancer in our patients.…”
Section: Treatment Details and Outcomessupporting
confidence: 89%
“…In comparison, in Eastern Morocco, lung cancer ranked the fourth most common cancer, accounting for 7.5% of total cancers and the most frequent malignancy with 19% of male cancers 29 . In Algeria, lung cancer is the sixth most common type of cancer (2.8%), and it is the most prevalent cancer in males representing 19.9% of cases 30 .…”
Section: Discussionmentioning
confidence: 96%
“…Khalis et al showed that BC incidence increased from 35 to 39 per 100000 women during 2004 to 2008 in Morocco 5. Another study which was done at the eastern morocco announced BC incidence was increased from 23 to 36.8 between 2006–2012 because of some reasons like late age of marriage, reducing fertility, change in diet, physical activity and change in prevalence of protective factors like age at the first child delivery and duration of breast feeding 17 , 18 . The incidence of BC was increased in Tunisia from 23.4 to 28.3 per 100000 that showed annual increase of 2.2% from 1993 to 2006.…”
Section: Discussionmentioning
confidence: 99%